Sex differences in immune cells: mechanistic perspectives and clinical correlates in physiology and disease - Liao, Ximing; Wu, Di; Gao, Jing; Xie, Fengyang; Li, Zhaoqi; Wang, Muyun; Wang, Kun; Gao, Yixuan; Li, Qiang; Gao, Wei (Frontiers in Immunology, 2026)
For decades, sex disparities have been acknowledged to influence immune regulation in health and disease throughout the life span, and contribute to variations in epidemiology, pathophysiology, manifestation, progression, and therapeutic response in multiple disorders. However, the underlying cellular and molecular mechanisms governing these disparities remain understudied. This review articulates the effects of sex as critical regulators of the major causes of morbidity and mortality in diseases. We summarize the key factors driving sex differences, including sexual hormones and sex chromosomes, as well as elaborate how these factors influence physiology and disease, especially by modulating the function and fate of immune cells. Our aim is to disentangle the intricacies of sexually-differentiated immune responses within physiological and pathological contexts, thereby establishing the groundwork for precision medicine approaches customized to sex-specific requirements in clinical settings.